The Effect of Financial Literacy on Students’ Investment Behavior: A Case Study of Uganda Christian University - Main Campus - Mellisa Auleria Nassaka (Uganda Christian University, 2024)
The purpose of the study was to find out the Effect of Financial Literacy on Students’ Investment Behavior focusing on Uganda Christian University-Main campus as a case study. The study was guided by three objectives firstly to find out how knowledge about financial products affects students’ investment behavior, secondly to find out how access to financial products affects students’ investment behavior and lastly to find out how financial skills influence students’ investment behavior. The study employed a cross-sectional research design with a quantitative methodology. The population was Bachelor of Business Administration students who were in their third year second semester totaling 163 students. The study adopted the use of a simple random sampling technique. The sample size for the study was 118 students using the Krejcie and Morgan table. The study used questionnaires which was the main method of collecting the primary data required for the study. The data was first coded and Statistical Package for Social Sciences (SPSS) was used for analysis. Descriptive statistics techniques were used to analyze the data. The findings were presented in frequency tables and percentages. The results showed that knowledge about financial products contributes to students’ investment behavior as students with more financial knowledge about the products explore their options and take on investments. Furthermore, access to financial products significantly affects students’ investment behavior where the participants with better access to financial products are more likely to have better investment behavior as compared to those with less access to financial products. Additionally, financial skills can affect the investment behavior of students where those with better financial skills in planning and information are at an advantage of making better investment decisions. Conclusively, the study recommended mentorship and guidance programs for students to help them improve their financial skills and make better well-assessed investment choices to secure their future. Furthermore, further researchers should base studies on the influence of cultural factors on financial literacy levels and investment behavior.
Undergraduate research